Strategic Communication by the Indian Army: A Thematic Analysis of Press Releases Disbursed by Defence Public Relations (2019–2022) (International Journal of Environmental Sciences, 2025)
In modern times when information rules the era, strategic communication has surface as an important tool in correltion of military and national security objectives. The Indian Army operating in a complex geopolitical environment shaped by threats from not-so-friendly neighbours and hybrid warfare tactics, have gradually shifted from a tradition of operational restrain to enclasping conscious narrative-building through communication. This transformation has been led through the Directorate of Public Relations (DPR), Ministry of Defence, which is the organisation for shaping Indian Army’s public messaging. From 1999 Kargil War to 2020 Galwan Valley clash, key military operations have revealed a coming together of military actions and narrative strategies. Strategic messaging has not only aimed to reiterate deterrence and provide a filip to public morale but also to resist enemy disinformation , particularly from Pakistan's Inter-Services Public Relations (ISPR) and China’s state-controlled media. In this context, military communication is no longer an ancillary function but a strategic role with domestic and international implications as stated by Hallahan et al.(2007) and Verčič & van Dyke (2015).